Restorative Justice in the Handling of Minor Criminal Offenses: Effectiveness and Societal Challenges - Alexandra, Sallie; Alexa, Vinda Sari; Rosdiana, Rosdiana (LPPM Universitas Sains dan Teknologi Komputer, 2025)
Often, retributive approaches in Indonesia's criminal justice system have failed to address minor offenses fairly and efficiently. The study intends to assess the feasibility of restorative justice (RJ) in practice while also addressing the social and institutional challenges that come with handling minor cases in urban and semi-urban areas. Using qualitative methods within a descriptive-evaluative approach, it analyzes 10 real cases from East Jakarta and Depok involving 25 informants from five major stakeholder groups. Findings indicate that almost 80% of the cases were appropriately disposed of through community mediation, the results of which were satisfying to victims, fastened processes, and no harm caused to the offenders. On the contrary, there were some challenges, such as limited knowledge among law enforcement officers, a lack of training, and victims' disbelief in those solutions. It recommends success indicators defined from the culture of field practices and introduces a modeled policy for RJ in the Indonesian context. What makes this research novel is the cross-actor approach and theoretical integration that truly minimizes the gap between law-related formal regulations and restorer justice in practice.